(NkAMENNOE DYHANIE zEMLI (B:s (NwZGLQD NA PROBLEMY MOBILIZMA (B/s - (NkUZNECOW(B, (NpETR pAWLOWI^s; (NlAPUHOW(B, (Na(B.(Ns(B.s ((NnOWOSIBIRSK (B:s (NnAUKA(B. (NsIB(B. (NOTD(B-(NNIE(B,s, 1990)
(NbIBLIOGR(B.: (NS(B. 76 (10 (NNAZW(B.)s
(Nan sssr(B, (NsIB(B. (NOTD(B-(NNIEs
Keywords: (NdINAMIKAs; (NmATERIKIs